2022
DOI: 10.1111/jac.12613
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic activity and water use efficiency of Salvia verbenaca L. under elevated CO2 and water‐deficit conditions

Abstract: Investigating the combined effects of elevated CO2 concentration and water‐deficit on weed plants is crucial to gaining a thorough understanding of plant performance and modifying agricultural processes under changing climate conditions. This study examined the effect of elevated CO2 concentration and water‐deficit conditions on leaf gas exchange, water use efficiency, carboxylation efficiency and the photosystem II (PSII) activity of two Salvia verbenaca L., varieties. These varieties were grown under two CO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…It has been reported that stomatal conductance is lower under eCO 2 than under aCO 2 (Javaid et al. 2022; Zhang et al. 2024), which can be attributed to reduced water transpiration and improved water‐use efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that stomatal conductance is lower under eCO 2 than under aCO 2 (Javaid et al. 2022; Zhang et al. 2024), which can be attributed to reduced water transpiration and improved water‐use efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Water use was significantly reduced by eCO 2 at 47 DAT, and at the final harvest, water use was significantly lower under eCO 2 , especially under HC (Figure 6A-D). It has been reported that stomatal conductance is lower under eCO 2 than under aCO 2 (Javaid et al 2022;Zhang et al 2024), which can be attributed to reduced water transpiration and improved water-use efficiency. In this study, reduced water use is most likely due to shortened lifespan, as water use was positively correlated with lifespan, and the reduction in water use was much greater at T3 than at T1 and T2 (Figures 6A-D and 7).…”
Section: The Eco 2 -Induced Senescence Reduced Water Use Without Redu...mentioning
confidence: 98%
“…Крім того, з підвищенням вмісту СО 2 в повітрі рослини ефективніше використовують воду, поживні речовини і світлову енергію [53]. Підвищена концентрація СО 2 пом'якшує несприятливі наслідки дефіциту води, підвищує ефективність її використання [54][55]. Це може посилити конкурентоспроможність деяких видів бур'янів порівняно з іншими рослинами за посушливих умов.…”
unclassified